Daya saing dan determinan permintaan ekspor minyak sawit Indonesia ke China - Khairul Asrori; Haryadi Haryadi; Heriberta Heriberta (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze: 1) the competitiveness of Indonesian palm oil exports in the Chinese market; 2) factors that influence the demand for Indonesian palm oil exports to China. The data used are secondary time series data for the period 2000 - 2010. Data is sourced from the Central Bureau of Statistics, Foreign Trade Statistics, Indonesian Economic and Plantation Statistics, Ministry of Agriculture, Ministry of Trade, Indonesian Oil Palm Research Institute, Malaysian Palm Oil Board, Oil World Annual Report. To analyze export competitiveness using the RCA model, while analyzing the factors that influence exports using multiple linear regression models. The results of the study found: 1) During the period 2000 - 2010 Indonesian CPO exports to China already had competitiveness which was high above the world average market share; 2) Simultaneously and partially, the rupiah exchange rate against the US dollar, the population and the price of soybean oil have a significant effect on Indonesian CPO exports to China.